2019
DOI: 10.1111/nmo.13748
|View full text |Cite
|
Sign up to set email alerts
|

Peppermint and caraway oils have muscle inhibitory and pro‐secretory activity in the human intestine in vitro

Abstract: Background: Herbal medicinal products with a broad activity spectrum may be promising alternatives to treat functional gastrointestinal disorders (FGD). Menthacarin ® is a drug with a fixed combination of peppermint and caraway oils, which is clinically used to treat FGD-associated symptoms. Materials:We studied the effects of peppermint and caraway oils on contractile and secretory activity in 255 human small and large intestinal preparations derived from surgical resections (73 patients). Motility was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…Its only antipode namely (-)-Carvone has been reported as antispasmodic in guinea pig ileum by reducing contractions induced by histamine, carbachol and BaCl 2 (Souza et al, 2013). Moreover, caraway fruit extract stimulated the proximal and distal stomach motility in the guinea pig (Krueger et al, 2020). Furthermore, antagonism of irritable colon/stomach and diarrheal conditions by use of F. vulgare in folklore and Ayurvedic medicine system has been emphasized (Badgujar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Its only antipode namely (-)-Carvone has been reported as antispasmodic in guinea pig ileum by reducing contractions induced by histamine, carbachol and BaCl 2 (Souza et al, 2013). Moreover, caraway fruit extract stimulated the proximal and distal stomach motility in the guinea pig (Krueger et al, 2020). Furthermore, antagonism of irritable colon/stomach and diarrheal conditions by use of F. vulgare in folklore and Ayurvedic medicine system has been emphasized (Badgujar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological effect of these two essential oils on the digestive process and gastrointestinal motility have already been the subject of careful non-clinical and clinical studies. In various basic science studies as well as in human pharmacological studies, a spasmolytic action on smooth muscle was demonstrated for peppermint oil due to its calcium-antagonistic properties, while caraway oil shows antimeteoric and choleretic effects and decreases the muscular tone [18,19,20,21,22,23]. Moreover, peppermint oil has shown choleretic [24] and direct analgesic properties through inhibition of voltage-gated sodium channels [25,26] and activation of the cold receptor TRPM8 [27].…”
Section: Introductionmentioning
confidence: 99%
“…In specimens of surgically resected human intestines, peppermint oil as well as caraway oil inhibited muscle contractility, as indicated by sustained muscle relaxation and decrease in phasic contractility. These effects occurred in small and large intestinal preparations by inhibition of L-type calcium channels [11]. Normalizing motility by reducing spasms contributes to reduced intensity or elimination of epigastric and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of peppermint oil and caraway oil is of particular interest in FD and IBS because the reported mechanistic studies suggest a synergistic as well as an additive effect of the combination against the sensation of abdominal pain and bloating by a multitarget approach [11][12][13][14][15][16]. The German IBS guideline [17] specifically recommends peppermint oil for the treatment of pain and bloating due to its proven efficacy.…”
Section: Introductionmentioning
confidence: 99%